OPPORTUNITIES AND BARRIERS THE IMPLEMENTATION OF DIGITAL HEALTH APPLICATIONS IN INDONESIA - Abdillah Azis; Kamal Burhanuddin; Dian Budi Santoso (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2017)
The research method used is literature study and data collection and analysis. The search is limited to articles published from 2007-2017 in both Indonesian and English. The collection of data and analysis of articles and statistics from authorized agencies is summarized and presented in the SWOT group table format (Strengths, Weaknesess, Opportunities, Threats). Indonesia has the strength of the vision mission of the Ministry of Health, the number of Health care facilities, the number of doctors, SIK roadmap 2015-2019. Weaknesses in the form of limited number of BTS. Opportunities in the form of non-contagious disease rate, uneven doctors, economic growth, mobile phone ownership, Indonesian population, broadband villages. Barriers include high gini ratio, government regulation, electricity availability. Digital health applications have the potential to become a tool to improve health status in the community. This research is to analyze whatever opportunities and obstacles in the implementation of digital health applications in Indonesia. Ministry of Health as the official government institution should optimize the strength and minimize the weakness to take strength and avoid barriers in the implementation of digital health applications in Indonesia